Population Of Equids In The Community Of Gironda, Municipality Of Jerônimo Monteiro, Espírito Santo, Brazil - Ueldiane Quintiliano Lins; Jeferson Luiz Ferrari (Boletim de Indústria Animal, 2022)
The Equidae family has one genus, Equus. In this genus, the species are distributed between wild (Equus zebra) and domesticated (Equus caballus, Equus asinus). The animals of the genus Equus that underwent domestication over the centuries are horses and donkeys. With the development of cars, motorcycles and agricultural machinery, these animals have suffered a population decline in rural areas, mainly in small properties, making them almost non-existent in such farms. Due to the importance these animals still have in society, this study aimed to survey the equine population of existing in the Community of Gironda, municipality of Jerônimo Monteiro, state of Espírito Santo, Brazil. Fieldwork was carried out to identify and quantify the species and sexes of Equidae in the community. The location of the species was georeferenced using a GNSS receiver (GPSMAP64S). Photographic records were also made. Then, with a Geographic Information System program (QGIS 3.16.6), the study area was delimited, layers were created, and the spatial and quantitative distribution of the animals was analyzed for the elaboration of a map of the community€™s equine population. All mapping procedures were performed with the aid of the  SIRGAS 2000 Coordinate Reference System - UTM Zone 24S. We found that the animals are present in 10 locales in the Gironda community. The locales where the presence of horses was identified corresponded to Córrego Fundo; Gironda (divided between three sites: Anselmo, Almir and Jambo); Sítio Wilson Louzada; Vista Alegre; Sítio Zé Garcia; Sítio Wilson Garcia; Sítio Binoti; Sítio Marãmba; Serro; and Figueira. The total number of animals was 33 (24 females and 9 males), numbers considered low. Serro was the location that had the largest number of animals, with three geldings, one breeder and two mares. The breeder was kept apart from the females by confinement in a stall. We observed that the Gironde community has a greater number of fertile than infertile females, as well as more horses than donkeys, which allows us to hypothesize that in this community there is greater reproduction and succession of horses. However, the vast majority of horses had been neutered and pregnancies are long, which can compromise the evolution of the population. The results achieved in this survey point to the need to conduct research to expand knowledge about the equine population of small properties in the state of Espírito Santo, given the importance of these animals for leisure, therapy and work. It should be noted that the Gironda community is rural and, so some of these animals could be used or trained for animal traction, an economic alternative to machines, to draw farm implements and transport agricultural inputs, in addition to assisting in the management of cattle.